Simulation studies of divertor detachment and critical power exhaust parameters for Japanese DEMO design. (March 2021) - Asakura, N.; Hoshino, K.; Homma, Y.; Sakamoto, Y.; ,
Highlights: Simulation study for the divertor design of Japanese fusion DEMO reactor. Systematic scans of critical power exhaust parameters for the divertor operation. Heat load and detachment plasma profiles were evaluated in the low density condition. Restrictions of the divertor operation under more severe conditions were determined. Abstract: Handling of a large thermal power exhausted from the confined plasma is one of the most important issues for ITER and DEMO. A conventional divertor, which has the closed geometry similar to that of ITER and longer leg of 1.6 m, was proposed for the Japanese (JA) DEMO reactor ( R p / a p  = 8.5/2.42 m). A radiative cooling scenario of Ar impurity seeding and the divertor performance have been demonstrated by SONIC simulation, in order to evaluate the power exhaust in JA-DEMO 2014 (primary design with P sep  ~ 283 MW) and JA-DEMO with higher plasma elongation (a revised design with P sep  ~ 235 MW). The divertor operation with the peak q target  ≤ 10 MWm −2 was determined in the low n e sep of 2–3 × 10 19 m −3 under the severe conditions of reducing radiation loss fraction, i.e. f* rad div = ( P rad sol  +  P rad div )/ P sep, and diffusion coefficients ( χ and D) . The divertor geometry and reference key parameters ( f* rad div  ~ 0.8, χ  = 1 m 2 /s and D  = 0.3 m 2 /s) were so far consistent with the power exhaust concepts in the n e sep range, and the revised JA-DEMO design has advantages of wider n e sep range and enough margin for the divertor operation. For either severe assumption of f* rad div  ~ 0.7 or χ and D to the half value, higher n e sep operation was required for the primary design in order to control the peak q target  ≤ 10 MWm −2, i.e. the operation window was reduced. Applying the two severe assumptions, the divertor operation was difficult in the low n e sep range for the both designs.